Unpacking the Kurikulum Merdeka in Acehnese Schools: Implementation and Challenges in Foreign Language Education - Husna, Faizatul; Armawi, Sullati; Masuwd, Mowafg Abrahem; Huyen, Phan Thanh (Journal of Languages and Language Teaching, 2025)
This study investigates the implementation of the Kurikulum Merdeka to improve students' foreign language proficiency and examines the challenges faced by language teachers in its application within Acehnese schools. The selected schools represent diverse geographical contexts, including urban, suburban, and boarding schools, allowing for a comparative analysis of implementation strategies. In-depth, semi-structured interviews with ten foreign language teachers (English and Arabic), school principals, and staff provided qualitative data, supplemented by field notes, class discussion transcriptions, and textbook reviews. Findings show disparities in curriculum implementation by school type and location, with challenges including limited resources, insufficient training, and complexity, especially in under-resourced schools. However, the curriculum's student-centered, goal-oriented approach is seen as transformative for language classrooms. This study contributes to the literature on curriculum implementation and language education as well as providing insights for educational policymakers. It also provides practical recommendations for improving the integration of the Kurikulum Merdeka in Acehnese schools and ensuring its successful adoption in language education.